On certain infinite series and definite integrals - Bassali, W. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
The object of this paper is to obtain the sums of certain infinite series and evaluate certain new definite integrals with simple functions. Two combinatorial identities are obtained.